2021
DOI: 10.1111/jfpp.15217
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacities and betacyanin lc‐ms profile of red‐fleshed dragon fruit juice ( hylocereus polyrhizus ) extracted by ultrasound‐assisted enzymatic treatment and optimized by response surface methodology

Abstract: For the enhancement of betacyanin and phenolic compounds, that is, health-beneficial antioxidants, in red-fleshed dragon fruit, the response surface methodology (RSM) was employed using the Box-Behnken design to determine the combined effects of ultrasonic and enzymatic treatments on the maximization of their contents in the fruit juice. The optimal condition including 18.4 min of sonication and 88.5 min of enzymatic treatment at 33.0°C was obtained for the highest release of betacyanins, while those values we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
1
11
0
1
Order By: Relevance
“…Both peel and flesh samples exhibited a decrease in total phenolic amounts after 5 min of sonication. Similar reduction in fruit juice with sonication for a long time was reported by Le & Le (2021). The exposing to ultrasound for a long time and high sonication wave could lead to form of the more reactive oxygen species, which oxidised the phenolics and caused loss of antioxidants (Yeoh & Ali, 2017).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Both peel and flesh samples exhibited a decrease in total phenolic amounts after 5 min of sonication. Similar reduction in fruit juice with sonication for a long time was reported by Le & Le (2021). The exposing to ultrasound for a long time and high sonication wave could lead to form of the more reactive oxygen species, which oxidised the phenolics and caused loss of antioxidants (Yeoh & Ali, 2017).…”
Section: Resultssupporting
confidence: 87%
“…For flesh of pitaya, the catechin contents reached their maximum levels when sonicated for 30 min under atmosphere condition (8.35 mg per 100 g), and sonicated for 5 min under vacuum (9.35 mg per 100 g). Ultrasound‐assisted extraction had effect on phenolic compounds probably due to change in enzyme activities (Le & Le, 2021). Moreover, gallic acid content of flesh remained constant after sonication process.…”
Section: Resultsmentioning
confidence: 99%
“…The analyses of each peak, including retention time, [M + H] + ions, and MS 2 fragments, are summarised in Table 1. These compounds were identified from mass spectrometry (MS) results and after comparison with other literature (García‐Cruz et al ., 2017, Le & Le, 2021, M. Herbach et al ., 2004). We found that the earliest eluted betalain was betanin (betanidin 5‐O‐β‐glucoside), which is one of the most common betalains and has been identified in twenty‐four different plant parts (Martins et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant capacity of individual RPB was determined after dissolving in the same volume of deionised water. In red–purple pitaya, betalains can be considered one of the primary contributors to the free radical scavenging ability (Le & Le, 2021). By comparison, we can see that the contribution of betalains was determined.…”
Section: Resultsmentioning
confidence: 99%
“…High‐performance liquid chromatography‐high resolution mass spectrometry (LC‐HRMS) is a detection technology with high separation efficiency, high selectivity, and high sensitivity. It can solve the difficulties caused by the complex and trace composition of the substance to be identified (Le & Le, 2021; Silva et al., 2020). In this study, LC‐HRMS was used to analyze the chemical constituents of flavonoids in distillers' grains extract, and to identify the flavonoids.…”
Section: Introductionmentioning
confidence: 99%